[PP.04.30] PRESERVED CARDIOVASCULAR PERFORMANCE AND OPTIMAL HEART RATE CONTROL IN PATIENTS WITH POST-ISCHEMIC LEFT VENTRICULAR DYSFUNCTION TREATED WITH IVABRADINE FOR ONE YEAR. (September 2017) - Cesario, V.; Calvez, V.; Montefusco, M.; Brogna, F.; Volpe, M.; Savoia, C.
Abstract : Objective: Ivabradine may contribute to reduce heart rate (HR) in patients with cardiovascular disease. We sought to define the role of ivabradine on cardiovascular performance in patients with left ventricular (LV) dysfunction after myocardial infarction (MI). Design and method: We studied 16 patients with LV dysfunction after MI (NYHA II). The patients were in optimal standard treatment (including beta-blockers) for ischemic heart disease and heart failure. They were divided into two groups: one received ivabradine (IVA, n = 7, 5 to 7.5 mg bid) on top of the standard therapy; the other group received up-titration of the beta-blocker (BETA, n = 9), in order to reach HR <65 bpm. Both groups were followed for 1 year. Routinely clinic visits were performed every three months. The parameters derived by tonometric analysis of the pulse waveform (central blood pressure-cBP-, carotid-femoral-pulse-wave-velocity-cfPWV-) and those derived from echocardiography: ejection fraction (EF-for systolic function), E/e' (for diastolic function), and LV end diastolic volume (LV-eDV) were evaluated at beginning and after one year. Results: Both groups were similar for sex, age, BMI, and risk factors. HR was similar in both groups at beginning and it was decreased after one year only in IVA (66, 4 ± 3.58bpm reduced-to 50, 6 ± 1.17bpm, P < 0.05), and not in BETA (68.56 ± 4.39bpm vs 67.25 ± 4.17bpm). Peripheral (pBP) and central (cBP) blood pressure were similar at basal in BETA vs IVA (pBP:112, 7 ± 4.69/70, 22 ± 3.54mmHg vs 116.1 ± 4.2/67, 7 ± 2.2mmHg; cBP:103, 2 ± 5.23/70, 78 ± 3.52mmHg vs 105.0 ± 4.3/68, 57 ± 2.17mmHg) and were increased after one year only in BETA (pBP:135 ± 2.89/83, 75 ± 4.73mmHg vs basal, P < 0.05; cBP:124.5 ± 4.48/84, 5 ± 4.97 mm/Hg vs basal, P < 0.05). cfPWV was similar at beginning in both groups and it was increased only in BETA after one year (BETA:7 ± 0.5m/s increased-to 9.3 ± 0.9m/s, p < 0.05; IVA:7.5 ± 0.1m/s to 7.8 ± 0.7m/s, NS). EF, LV-eDV, and E/e' were similar in BETA vs IVA (46.2 ± 2.8% vs 48.4 ± 2.6%; 179.6 ± 10.2 ml vs 162 ± 10.6 ml, and 6.1 ± 0.6 vs 7.6 ± 0.7, respectively) and did not change over time. Conclusions: Ivabradine reduced HR more efficaciously with no hemodynamic effect, the uptitration of beta-blocker was less effective in reducing HR after one year follow-up in patients with LV dysfunction post-MI. This was associated with increased aortic stiffness. Thus, ivabradine seems highly effective in reducing HR in post-ischemic patients with LV dysfunction.